Implementasi Total Quality Manajemen pada Bank Syariah Indonesia KCP Gresik Menganti - Af’idatul Maulidiyah; Dian Aprissa M; Fakhriyadi Ainiyah; Bakhrul Huda (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2022)
Total Quality Management (TQM) is a starting point for an approach that assists Islamic financial institutions in improving service quality and regulates how the management control methods used are compatible with the management of financial institutions. This article wants to answer how the TQM concept is at BSI KCP Gresik Menganti and how TQM is implemented in that place. This research is a type of empirical research that emphasizes data collection directly from practice. The approach used by us is a qualitative approach. The results of our study are that the TQM concept in the research location emphasizes 1) friendly, courteous, and friendly service; 2) innovation is an initiative that implements solutions and wants to create added value; 3) role models, as actions and motivations that are correct and appropriate to implement cultural values; 4) professionalism, namely competence and responsibility, as well as innovative work, and; 5) honest, discipline, and consistency. In practice, BSI KCP Gresik Menganti implements TQM in the services provided which are pretty good, and most importantly the services provided do not look at who comes from both a race and ethnic perspective, the customers who come with various obstacles to BSI KCP Gresik Menganti.